Summary Judgment : its application in Malaysia / Abd. Aziz Mohd Yusuff - Mohd Yusuff, Abd. Aziz (1987)
This project paper on summary Judgment and It Application in Malaysia is intended to discuss the application of the Summary Judgment Order or commonly known as Order 14 Judgment in Malaysia generally. It laid down the object and the procedure in application of Summary Judgment whether in High Court or in Subordinate Court. In addition, in earlier chapter of this project paper is in the light of the development, historical and application of the Order 14 Judgment into the Malaysian Courts. The remainder of this paper included the usage and the procedure in application for Order 14 Judgment.